ASA BUNDA (Aksi Sehat Anak bersama Bunda): Maternal Educationto Prevent Stunting in Bangun Rejo - Yasmine Naura Aurelya; Nadhirah Shahira Nur; Muhamad Rayhan Adira Damanik; Regina Anindya Putri; Thisna Nugra Asysyifa; Ilmawari Ilmawari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Stunting is still a major health issue in Bangun Rejo Village. Most mothers still lack understanding of balanced nutrition and the impact of early marriage on child growth. This issue is important because mothers play a central role in ensuring optimal child development. However, health education programs focusing on maternal knowledge and reproductive health are still limited in this area. Therefore, the ASA BUNDA program was designed to fill this practical gap by providing direct education to improve mothers’ understanding and awareness in preventing stunting. The ASA BUNDA aims to raise mothers' awareness of stunting prevention and the need of delaying early marriage. The event took place on July 17, 2025, engaging mothers and youth health cadres of the Posyandu Remaja in Bangun Rejo. Health education sessions were conducted interactively by students and public health lecturers. A pre-test and post-test were used to measure changes in knowledge, and the data were analyzed using the Wilcoxon Signed-Rank Test to determine significance. The program had 85% attendance and a considerable increase in participants' post-test knowledge ratings. Statistical analysis using the Wilcoxon Signed-Rank Test revealed a significant difference between pre-test and post-test results (p < 0.05), showing better awareness of stunting prevention and parenting practices. Participants also provided favorable feedback and demonstrated a readiness to apply their knowledge in everyday family health activities. The ASA BUNDA program significantly enhanced mothers' understanding of stunting prevention and healthy parenting practices. This activity shows that empowering mothers through simple and participatory health education can help reduce stunting risk in the community